2018
DOI: 10.1016/j.scr.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Inverse agonism of retinoic acid receptors directs epiblast cells into the paraxial mesoderm lineage

Abstract: We have investigated the differentiation of paraxial mesoderm from mouse embryonic stem cells utilizing a Tbx6-EYFP/Brachyury (T)-Ckerry dual reporter system. Differentiation from the mouse ESC state directly into mesoderm via Wnt pathway activation was low, but augmented by treatment with AGN193109, a pan-retinoic acid receptor inverse agonist. After five days of differentiation, T+ cells increased from 12.2% to 18.8%, Tbx6+ cells increased from 5.8% to 12.7%, and T+/Tbx6+ cells increased from 2.4% to 14.1%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(94 reference statements)
1
2
0
Order By: Relevance
“…A potential target that is repressed by Rarγ2 might be ripply2, a repressor of tbx6; therefore, promoting tbx6 expression [98,99]. Similar results were obtained in a study that differentiated mouse ESCs via Wnt pathway activation [100]. Here the pan-RAR inverse agonist AGN193109, which stabilizes the heterodimeric complex of RA receptors (RAR/RXR) with their transcriptional co-repressors, was applied to inhibit RA signaling during ESC differentiation, beginning at a differentiation stage that corresponds to cells from the CLE.…”
Section: Ra Signaling Controls Induction and Differentiation Of Neurosupporting
confidence: 81%
See 1 more Smart Citation
“…A potential target that is repressed by Rarγ2 might be ripply2, a repressor of tbx6; therefore, promoting tbx6 expression [98,99]. Similar results were obtained in a study that differentiated mouse ESCs via Wnt pathway activation [100]. Here the pan-RAR inverse agonist AGN193109, which stabilizes the heterodimeric complex of RA receptors (RAR/RXR) with their transcriptional co-repressors, was applied to inhibit RA signaling during ESC differentiation, beginning at a differentiation stage that corresponds to cells from the CLE.…”
Section: Ra Signaling Controls Induction and Differentiation Of Neurosupporting
confidence: 81%
“…A continued treatment with the inverse agonist eventually repressed the maturation of PSM into the somitic mesoderm. This suggests that RARs function in epiblast and early mesoderm progenitor cells-areas where RA is absent-to promote their differentiation into paraxial mesoderm lineage [100].…”
Section: Ra Signaling Controls Induction and Differentiation Of Neuromentioning
confidence: 99%
“…There are several published protocols for differentiation of human pluripotent stem cells (PSCs) into somites and their derivatives (Chal et al, 2015; Loh et al, 2016; Xi et al, 2017; Nakajima et al, 2018; Russell et al, 2018). A recent study using single-cell RNA-sequencing (scRNA-seq) analyses found that the cells pass through a transitory state that displays gene expression signatures similar to somitomeres before specifying into somite cells (Loh et al, 2016); however, no oscillatory gene expression pattern has been reported.…”
Section: Introductionmentioning
confidence: 99%